Editor's Notes - Verbuč, David (Lidé města, 2021)
Next year will be 15 years since we added English editions to Lidé města / Urban People (the journal itself has existed since 1999, and in its first seven years was only published in the Czech language). During these years of maturation, we have graduated into a high-quality interdisciplinary and international journal of urban anthropology, as we continue raising our standards. Part of this process of transformation involves some recent innovations that we initiated last year, which can also be directly or indirectly observed in our new issue (23/2).